1996
DOI: 10.1021/ma951696x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of Microphase-Separated A2B Simple Graft Copolymers

Abstract: The morphological behavior of a series of well-defined A2B simple graft or “Y” architecture block copolymers is characterized via small-angle X-ray scattering (SAXS) and transmission electron microscopy (TEM). This model architecture is formed by grafting a polystyrene block onto the center of a polyisoprene backbone. The volume fraction windows in which specific strongly segregated microphase-separated morphologies are observed are shifted to higher volume fractions of the PS graft material than in the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
171
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 24 publications
16
171
0
2
Order By: Relevance
“…Furthermore, worm-like micelles are observed in the DPD simulations [24] in contrast to the sphere or cylindrical phase in the SCFT near the disorder-order transition around φ B = 0.8. Also, experiments by Pochan et al [20] show the existence of microphase separated structures (micellar) without any underlying lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, worm-like micelles are observed in the DPD simulations [24] in contrast to the sphere or cylindrical phase in the SCFT near the disorder-order transition around φ B = 0.8. Also, experiments by Pochan et al [20] show the existence of microphase separated structures (micellar) without any underlying lattice.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1990s, systematic studies [19,20,21] aimed at elucidating the effect of branched architecture on the morphology and properties of block copolymers were initiated. Like the linear di-block copolymer melts, classical morphologies namely, lamellae, cylinders, spheres and gyroid, were observed in experiments [19,20,21] for the miktoarm star copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Changing from simple linear diblock copolymers to graft copolymers can greatly alter the dependence of the morphologies on the component volume fractions. [1][2][3][4][5][6][7][8][9][10][11] It has been shown that complex graft copolymer architectures with multiple grafting points ( Figure 1) can be understood morphologically by analogy to fundamental building blocks defined as the average structure per junction point. 12,13 This fundamental component of a larger graft molecular architecture is referred to as the constituting block copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Unique morphologies were found in branched and star block copolymers that are not observed for linear block copolymers. [35][36][37][38][39] At the air-water interface, the hydrophobic chains collapse into globules while the hydrophilic chains spreads out to form a brush-like or a flat (pancake-like) structures. [40][41][42][43][44][45][46][47] Hyperbranched molecules possess a tree-like structure similar to that of dendrimers with the same enhancement in chemical and physical properties but at a great reduction in cost and time of synthesis when compared with dendrimers.…”
mentioning
confidence: 99%